2021
DOI: 10.3389/fcomp.2021.531713
|View full text |Cite
|
Sign up to set email alerts
|

How the Visual Design of Video Game Antagonists Affects Perception of Morality

Abstract: The visual design of antagonists—typically thought of as “bad guys”—is crucial for game design. Antagonists are key to providing the backdrop to a game's setting and motivating a player's actions. The visual representation of antagonists is important because it affects player expectations about the character's personality and potential actions. Particularly important is how players perceive an antagonist's morality. For example, an antagonist appearing disloyal might foreshadow betrayal; a character who looks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…Research by Pradantyo et al examined the impact of character design on player attraction and engagement [8]. The study revealed that visually appealing and well-designed characters significantly influenced player enjoyment and emotional connection.…”
Section: Character Designmentioning
confidence: 99%
“…Research by Pradantyo et al examined the impact of character design on player attraction and engagement [8]. The study revealed that visually appealing and well-designed characters significantly influenced player enjoyment and emotional connection.…”
Section: Character Designmentioning
confidence: 99%